2023
DOI: 10.3390/diagnostics13040582
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Measuring Protocol for the Infraspinatus Muscle with M-Mode Ultrasound in Asymptomatic Subjects. Intra- and Inter-examiner Reliability Study

Abstract: M-mode ultrasound is a reliable and valid instrument for assessing muscle activity. However, it has not been studied in any of the muscles belonging to the shoulder joint complex, particularly in the infraspinatus muscle. The aim of this study is the validation of the infraspinatus muscle activity measurement protocol with the M-mode ultrasound in asymptomatic subjects. Sixty asymptomatic volunteers were evaluated by two physiotherapists who were blinded; each of them carried out three measurements with the M-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…Sicilia-Gomez et al [9] observed excellent reliability in diaphragm thickness measurements during tidal volume and expiration at forced volume in subjects with or without low back pain. Lastly, Ortega-Santamaría et al [10] utilized M-mode ultrasonography to evaluate various aspects of the infraspinatus muscle, measuring muscle thickness at rest and during contraction, as well as the velocity of muscle activation and relaxation. Muscle thickness measurements demonstrated good reliability, while activation and relaxation velocity showed moderate reliability.…”
mentioning
confidence: 99%
“…Sicilia-Gomez et al [9] observed excellent reliability in diaphragm thickness measurements during tidal volume and expiration at forced volume in subjects with or without low back pain. Lastly, Ortega-Santamaría et al [10] utilized M-mode ultrasonography to evaluate various aspects of the infraspinatus muscle, measuring muscle thickness at rest and during contraction, as well as the velocity of muscle activation and relaxation. Muscle thickness measurements demonstrated good reliability, while activation and relaxation velocity showed moderate reliability.…”
mentioning
confidence: 99%